2022
DOI: 10.3233/wor-210031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a 6-month mandatory military police academy training on recruits’ physical fitness

Abstract: BACKGROUND: Physical fitness for health and professional performance play important roles in police workforce considering that policing is a dangerous job, associated with high physical demands. OBJECTIVES: (1) To evaluate the effects of a 6-month course of police academy training on health-related physical fitness (HRPF) of military police recruits. (2) To investigate whether recruits’ HRPF still met the academy entry standards after an unsupervised 7-month period prior to academy. METHODS: We conducted an ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…W.G. Barbosa et al (2022) substantiate the professional suitability of a police officer to perform tasks with high physical activity. The experimental observational and longitudinal study confirmed that after six months of training at the academy, during which physical exercise was not the main goal, but its regularity was maintained, the cadets' physical fitness indicators continued to improve.…”
Section: ■ Ensuring Personal Safety Of a Police Officer In The Contex...mentioning
confidence: 83%
“…W.G. Barbosa et al (2022) substantiate the professional suitability of a police officer to perform tasks with high physical activity. The experimental observational and longitudinal study confirmed that after six months of training at the academy, during which physical exercise was not the main goal, but its regularity was maintained, the cadets' physical fitness indicators continued to improve.…”
Section: ■ Ensuring Personal Safety Of a Police Officer In The Contex...mentioning
confidence: 83%
“…W.G. Barbosa et al (2022) substantiate the professional suitability of a police officer to perform tasks with high physical activity. The experimental observational and longitudinal study confirmed that after six months of training at the academy, during which physical exercise was not the main goal, but its regularity was maintained, the cadets' physical fitness indicators continued to improve.…”
Section: ■ Ensuring Personal Safety Of a Police Officer In The Contex...mentioning
confidence: 83%